Structured decision making : a practical guide to environmental management choices - Gregory, Robin (Robin Scott) (Chichester, West Sussex ; Hoboken, N.J. : Wiley-Blackwell, 2012)
"This book is about the creative and messy process of making environmental management decisions. The approach we describe is called Structured Decision Making, a distinctly pragmatic label given to ways for helping individuals and groups think through tough multidimensional choices characterized by uncertain science, diverse stakeholders, and difficult tradeoffs. This is the everyday reality of environmental management, yet many important decisions currently are made on an ad hoc basis that lacks a solid value-based foundation, ignores key information, and results in selection of an inferior alternative. Making progress--in a way that is rigorous, inclusive, defensible, and transparent--requires combining analytical methods drawn from the decision sciences and applied ecology with deliberative insights from cognitive psychology, facilitation, and negotiation. We review key methods and discuss case-study examples based in our experiences in communities, boardrooms, and stakeholder meetings. Our goal is to lay out a compelling guide that will change how you think about making environmental decisions"--
Cover; Series page; Title page; Copyright page; Foreword; Preface; 1 Structuring Environmental Management Choices; 1.1 Three typical approaches to environmental decision making; 1.2 Structured decision making; 1.3 Case study: using structured decision making to develop and evaluate creative water-use strategies; 1.4 The art and science of decision making; 1.5 Key messages; 1.6 Suggested reading; 2 Foundations of Structured Decision Making; 2.1 Underlying concepts; 2.2 Comparison with other evaluation approaches; 2.3 Key messages.
Includes bibliographical references and index.
Print version record.
Keywords: Environmental management; Environmental management -- Case studies; Environmental management -- Decision making; MATHEMATICS -- Probability & Statistics -- General; BUSINESS & ECONOMICS -- Environmental Economics; BUSINESS & ECONOMICS -- Green Business; NATURE -- Natural Resources; Environmental management; Environmental management -- Decision making; Umweltbezogenes Management; Entscheidungsverhalten; Electronic books; Case studies